Cultural Capital and the Digital Divide: A Literature Review - Suzanne K. Becking; Marilyn L. Grady (The Advocate, 2012)
The internet holds promise of rapid diffusion of information to the global community and the potential to change our way of life. Those without access or with limited access to the internet are at a disadvantage. This paper examined the implications and issues surrounding the Digital Divide as it relates to Bourdieu's theory of cultural capital. It is an examination of the literature on the Digital Divide in education.